1997
DOI: 10.1073/pnas.94.21.11238
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-specific recognition of a subgenomic RNA promoter by a viral RNA polymerase

Abstract: RNA templates of 33 nucleotides containing the brome mosaic virus (BMV) core subgenomic promoter were used to determine the promoter elements recognized by the BMV RNA-dependent RNA polymerase (RdRp) to initiate RNA synthesis. Nucleotides at positions ؊17, ؊14, ؊13, and ؊11 relative to the subgenomic initiation site must be maintained for interaction with the RdRp. Changes to every other nucleotide at these four positions allow predictions for the base-specific functional groups required for RdRp recognition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
129
1
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(140 citation statements)
references
References 30 publications
(23 reference statements)
8
129
1
2
Order By: Relevance
“…Specific RNA recognition by proteins underlies many biological processes that demand high-fidelity performance+ In the best-described examples, highly specific outcomes are the result of the recognition of RNA elements that comprise short sequence-specific features placed in a defined structural framework+ Thus, specific aminoacylation of transfer RNAs by the cognate aminoacyl-tRNA synthetase requires the accurate placement of a few identity nucleotides within the generic tRNA structure that is approximately 76 nt long (Pallanck et al+, 1995)+ Shorter elements (ca+ 20-30 nt long) recognized by combined structural and sequence information are the helix/loop combinations bound by the HIV Tat protein (Puglisi et al+, 1992), phage R17/MS2 coat protein (Valegård et al+, 1994), and U1A spliceosomal protein (Oubridge et al+, 1994)+ This is not the only way in which proteins recognize specific sites on RNA, however+ For instance, evidence exists that the phage T4 translational repressor, regA, recognizes a consensus sequence of some 12-15 linear nucleotides in unstructured RNA (Szewczak et al+, 1991;Brown et al+, 1997)+ Here, as a result of studying the replication of a positive strand RNA virus, we report a further strategy for specific RNA recognition that requires a combination of a very short specific-sequence and adjacent non-or low-specificity secondary structure+ Positive strand RNA viruses replicate via two sequential transcriptional steps that synthesize full-length minus and plus sense genomes; additionally, in some viruses, internal initiation on the minus strand (Miller et al+, 1985) results in the synthesis of subgenomic RNAs that are collinear with the 39-region of the genomic RNA and that serve as mRNAs expressing downstream cistrons (Buck, 1996)+ Specific initiation sites are used for each of these transcriptional events, and a breakdown of the fidelity of initiation site selection would lead to truncated genomes and viral proteins+ The cisrequired promoter elements controlling these specific strand initiations have been studied in a number of viruses by in vivo approaches using deleted genomes and by in vitro approaches using viral RNA-dependent RNA polymerase (RdRp) preparations (Buck, 1996)+ These studies have generally supported the view that accurate transcription is controlled by the detection of specific features of either sequence or a combination of sequence and structure (e+g+, Miller et al+, 1986;Dreher & Hall, 1988;Levis et al+, 1990;Cui & Porter, 1995;Song & Simon, 1995;Miranda et al+, 1997;Siegel et al+, 1997)+ Against this backdrop of apparently specific recognition of defined, discrete promoter elements, we have studied the features directing minus strand synthesis by the turnip yellow mosaic virus (TYMV) RdRp+ Minus strand synthesis initiates specifically opposite the penultimate resi...…”
Section: Introductionmentioning
confidence: 87%
“…Specific RNA recognition by proteins underlies many biological processes that demand high-fidelity performance+ In the best-described examples, highly specific outcomes are the result of the recognition of RNA elements that comprise short sequence-specific features placed in a defined structural framework+ Thus, specific aminoacylation of transfer RNAs by the cognate aminoacyl-tRNA synthetase requires the accurate placement of a few identity nucleotides within the generic tRNA structure that is approximately 76 nt long (Pallanck et al+, 1995)+ Shorter elements (ca+ 20-30 nt long) recognized by combined structural and sequence information are the helix/loop combinations bound by the HIV Tat protein (Puglisi et al+, 1992), phage R17/MS2 coat protein (Valegård et al+, 1994), and U1A spliceosomal protein (Oubridge et al+, 1994)+ This is not the only way in which proteins recognize specific sites on RNA, however+ For instance, evidence exists that the phage T4 translational repressor, regA, recognizes a consensus sequence of some 12-15 linear nucleotides in unstructured RNA (Szewczak et al+, 1991;Brown et al+, 1997)+ Here, as a result of studying the replication of a positive strand RNA virus, we report a further strategy for specific RNA recognition that requires a combination of a very short specific-sequence and adjacent non-or low-specificity secondary structure+ Positive strand RNA viruses replicate via two sequential transcriptional steps that synthesize full-length minus and plus sense genomes; additionally, in some viruses, internal initiation on the minus strand (Miller et al+, 1985) results in the synthesis of subgenomic RNAs that are collinear with the 39-region of the genomic RNA and that serve as mRNAs expressing downstream cistrons (Buck, 1996)+ Specific initiation sites are used for each of these transcriptional events, and a breakdown of the fidelity of initiation site selection would lead to truncated genomes and viral proteins+ The cisrequired promoter elements controlling these specific strand initiations have been studied in a number of viruses by in vivo approaches using deleted genomes and by in vitro approaches using viral RNA-dependent RNA polymerase (RdRp) preparations (Buck, 1996)+ These studies have generally supported the view that accurate transcription is controlled by the detection of specific features of either sequence or a combination of sequence and structure (e+g+, Miller et al+, 1986;Dreher & Hall, 1988;Levis et al+, 1990;Cui & Porter, 1995;Song & Simon, 1995;Miranda et al+, 1997;Siegel et al+, 1997)+ Against this backdrop of apparently specific recognition of defined, discrete promoter elements, we have studied the features directing minus strand synthesis by the turnip yellow mosaic virus (TYMV) RdRp+ Minus strand synthesis initiates specifically opposite the penultimate resi...…”
Section: Introductionmentioning
confidence: 87%
“…Transcription by T7 RNA polymerase in vitro is currently the most widely used method to produce RNAs for a wide variety of applications, including structural and biochemical studies and potential therapeutics (Milligan et al+, 1987;Turek & Gold, 1990;Symensma et al+, 1996;Siegel et al+, 1997)+ Despite its usefulness, a number of undesired reactions increase the complexity of the T7 polymerase products and necessitate the careful purification of the desired RNAs+ These reactions include the synthesis of oligonucleotides aborted during the initiation of transcription (Martin et al+, 1988;Moroney & Piccirilli, 1991), polymerase slippage (MacDonald et al+, 1993), the use of alternative template initiation sites (Pleiss et al+, 1998;Helm et al+, 1999), and the addition of one or more nontemplated nucleotides at the 39 terminus of the nascent RNA (henceforth called the Nϩ1 activity)+ Nϩ1 activity can be a major contributing factor to heterogeneity in transcription products (Milligan et al+, 1987;Krupp, 1988)+ Previously, Moran et al+ (1996) demonstrated that DNA templates containing nucleoside with base analogs that cannot form hydrogen bonds with the substrate nucleotide can induce the termination of transcription prior to the nucleoside analog+ However, these analogs are not widely available and a significant amount of Nϩ1 activity remained with some templates+ We report that modification of either the penultimate nucleotide or the last two nucleotides at the 59 terminus of the DNA template with methoxy moieties at the ribose C29 position can significantly reduce Nϩ1 activity by the T7 RNA polymerase and, in several cases, increase the abundance of the desired RNA+…”
Section: Introductionmentioning
confidence: 99%
“…By analogy with BMV (Duggal et al 1994;Siegel et al 1997), it is likely that sequences upstream and downstream of the transcriptional start sites for the TMV subgenomic RNAs contribute to the activity of subgenomic promoters. proposed that A-U-rich sequences near the 5'-ends of the movement-protein and coat protein genes, termed Butler boxes, could be signal sequences for subgenomic RNA synthesis.…”
Section: Cis-acting Sequences Required For Tmv Rna Replicationmentioning
confidence: 99%
“…There is no evidence that subgenomic RNAs are self-replicating. TMV subgenomic RNAs are likely to be synthesized by internal initiation on genome-length negative-strand RNA templates, which requires subgenomic promoters containing sequences not found in the subgenomic RNA itself, as shown for brome mosaic virus (Miller et al 1985;Marsh et al 1988;Siegel et al 1997;Adkins et al 1998). Subgenomic double-stranded RNAs are therefore probably dead-end products formed as a result of synthesis of a negative strand on a subgenomic positive-strand RNA template.…”
mentioning
confidence: 99%